Long term left ventricular impairment after SARS-COV2 infection. (4th February 2022) - Brito, J; Silva, P; Valente Silva, B; Pereira, S; Silverio Antonio, P; Morais, P; Rigueira, J; Placido, R; David, C; Silva, D; Fernandes, S; Ribeiro, J; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The impact of acute infection by SARS-COV2 on the cardiovascular system has been previously reported in the literature, with a higher propensity in patients with more serious pattern of disease and pro-inflammatory status. Nevertheless, the long-term burden and sequels of COVID-19 on the cardiovascular system is still unknown. Purpose: To evaluate the long-term impact of COVID-19 on left ventricular function in patients with severe clinical presentation requiring intensive care hospitalization. Methods:   This was a single-center observational, prospective study which included patients requiring admission to the Intensive Care Unit (ICU) due to COVID-19 infection from January to November 2020. All discharged patients were contacted to perform a clinical, electrocardiographic and echocardiographic evaluation and those who accepted were included on the protocol. Baseline and clinical characteristics were collected from clinical reports. For the global longitudinal strain (GLS) analysis all patients with significant wall motion abnormalities and valvular cardiopathy were excluded. Statistical analysis was performed with Mann-Whitney and a safety cut-off was established with ROC curve analysis. Results:   A total of 43 patients were included (mean age 64 ± 12, 67.4% males). During SARS-COV2 infection 49% presented with severe ARDS and 51% with moderate, 35% required invasive mechanical ventilation, 14% noninvasive mechanical ventilation and 52% with high nasal flow cannula. On the follow-up analysis, fatigue was the most reported in symptom (52% patients) and the majority did not present other signs or symptoms suggestive of heart failure, with the mean NT-proBNP of 49 ± 389 pg/dL. The standard ECG and echocardiogram did not show significant changes with a mean LVEF of 58 ± 7.8 and mean TAPSE of 21 ± 4. The strain analysis showed low value of GLS (mean GLS of -17.14 ± 2.36) for a reference cut-off of -18%, suggesting subclinical left ventricular dysfunction in this subset of patients with preserved ejection fraction. Maximum CPR values during ICU did not correlate either with the extent of disease evolvement in CT (p= NS) or ARDS severity (p= NS). Nevertheless, maximum CPR correlated significantly with GLS reduction (R = 0.44, p = 0.019). A CPR value higher than iger30mg/dL had 100% specificity for GLS reduction and a cut-off of 14gm/dL reported a sensitivity of 65% and specificity pf 75% for reduction in GLS. Conclusion: In our study, we reported subclinical impairment in left ventricular function detected with global longitudinal strain after serious infection with SARS-COV2. The detected myocardial dysfunction was related with higher inflammatory as expressed by CPR values. Long-term monitoring of these patients should be undertaken in order to timely detect late complications.